PENGEMBANGAN SISTEM INVENTARIS CRUDE OIL DENGAN SCRUM PADA PASIR PETROLEUM RESOURCES LIMITED - Putra Setyo, Excsell Edo; Ihsan Alfani Putera, Muhammad; Deny Arthawan Sugih, I Putu (Jurnal Rekayasa Perangkat Lunak dan Sistem Informasi, 2023)
Inventory or office stock is an activity or action to carry out calculations, arrangements, management, implementation of recording of an item to obtain information that can be controlled and supervised on a company's assets. Companies often get difficulties or difficulties in controlling an asset so that they make reports regarding the identity of these assets irregularly. Under these conditions, the company really needs to develop a manual asset recording report process that is computerized by building an inventory information system that can manage and record the activities of a company's assets. The research method used is the Agile Method, the Scrum framework model. By building a Website-based Asset Inventory System and Page Hypertext Processor as the Boostrap Framework programming language as the End font framework and MySQL as a database server, it is hoped that the Asset Inventory Information System can be useful for companies in controlling and recording an identity of goods or assets.